Establishment of a mast cell line, NCL‐2, without Kit mutation, derived from NC mouse bone marrow. Issue 1 (2nd April 2014) - Hiragun, Takaaki; Yanase, Yuhki; Okabe, Tsutomu; Hiragun, Makiko; Kawai, Mikio; Hide, Michihiro
Abstract : Immortal mast cell lines, such as RBL‐2H3 and HMC‐1 cells, are commonly utilized to investigate the function of mast cells. However, they are tumor cells carrying a gain‐of‐function mutation of Kit . We established an immortal mast cell line without Kit mutation, NCL‐2, derived from NC mouse bone marrow. NCL‐2 cells could be maintained without additional growth factors and thus could respond to exogenous growth signals. Moreover, NCL‐2 cells expressed FcεRI and KIT, and release histamine and LTB4 in response to antigen stimulation. This cell line could be a useful tool to analyze proliferation, differentiation, and function of normal mast cells. Abstract : We established an immortal mast cell line without Kit mutation, NCL‐2. NCL‐2 cells could be maintained without additional growth factors. NCL‐2 cells expressed FcεRI and released histamine and LTB4 in response to antigens. NCL‐2 cells were tumorigenic but much less aggressive than P815 mastocytoma.